A New Fast Method for Detecting and Validating Horizontal Gene Transfer Events Using Phylogenetic Trees and Aggregation Functions - Badescu, Dunarel; Tahiri, Nadia; Makarenkov, Vladimir (Pattern Recognition in Computational Molecular Biology, 2015)
This chapter presents a new algorithm, called horizontal gene transfer (HGT)‐QFUNC, for detecting genomic regions that may be associated with complete HGT events, using phylogenetic trees and aggregation functions. It provides the details of the method for inferring complete HGT events. The chapter validates the obtained results with p‐values calculated using a Monte Carlo approach. The advantage of the proposed algorithm is its quadratic time complexity on the number of considered species. The chapter then estimates the rates of complete HGT among prokaryotes comparing the results to the highly accurate, but much slower, HGT‐Detection algorithm based on the calculation of bootstrap support of considered gene trees. It compares the results provided by HGT‐QFUNC and HGT‐Detection using simulated data, which will be representative of the prokaryotic landscape. The chapter finally shows that the proposed new functions and algorithm are capable of providing good detection rates for the highly probable HGT events.